Basic research in information science and technology for air force needs (National Academies Press, 2006)
The U.S. Air Force is developing new force capabilities appropriate to an emerging array of threats. It is clear that advances in information science and technology (IS & T) are essential for most of these new capabilities. As a consequence, the Air Force is finding it necessary to refocus its IS & T basic research program to provide stronger support for reaching these goals. To assist this effort, the AFOSR asked the NRC for a study to create a vision and plan for the IS & T-related programs within the Office & rsquo;s Mathematics and Space Science Directorate. This report provides an assessment of basic research needs for Air Force systems and communications, software, information management and integration, and human interactions with IS & T systems. The report also offers a set of priorities for basic IS & T research, and an analysis of funding mechanisms its support.